Effect of aberrant DNA methylation on cancer stem cell properties - Mazloumi, Zeinab; Farahzadi, Raheleh; Rafat, Ali; Dizaji Asl, Khadijeh; Karimipour, Mohammad; Montazer, Majid; Movassaghpour, Ali Akbar; Dehnad, Alireza; Nozad Charoudeh, Hojjatollah (Experimental and molecular pathology, 2022)
DNA methylation, as an epigenetic mechanism, occurs by adding a methyl group of cytosines in position 5 by DNA methyltransferases and has essential roles in cellular function, especially in the transcriptional regulation of embryonic and adult stem cells. Hypomethylation and hypermethylation cause either the expression or inhibition of genes, and there is a tight balance between regulating the activation or repression of genes in normal cellular activity. Abnormal methylation is well-known hallmark of cancer development and progression and can switch normal stem cells into cancer stem cells. Cancer Stem Cells (CSCs) are minor populations of tumor cells that exhibit unique properties such as self-regeneration, resistance to chemotherapy, and high ability of metastasis. The purpose of this paper is to show how aberrant DNA methylation accumulation affects self-renewal, differentiation, multidrug-resistant, and metastasis processes in cancer stem cells. DNA methylation controls stem cell fate, and aberrant methylation induces CSCs formation that has a role in self-regenerate, metastasis, and drug resistance. [Display omitted] •Abnormal methylation creates cancer stem cells.•Aberrant methylation has a role in self re-newel of cancer stem cells.•Abnormal methylation is responsible for drug-resistance in cancer stem cells.•Alterations in normal methylation patterns induces metastasis of cancer stem cells.